2016
DOI: 10.1136/gutjnl-2016-312431
|View full text |Cite
|
Sign up to set email alerts
|

Current and upcoming pharmacotherapy for non-alcoholic fatty liver disease

Abstract: Given the high prevalence and rising incidence of non-alcoholic fatty liver disease (NAFLD), the absence of approved therapies is striking. Although the mainstay of treatment of NAFLD is weight loss, it is hard to maintain, prompting the need for pharmacotherapy as well. A greater understanding of disease pathogenesis in recent years was followed by development of new classes of medications, as well as potential repurposing of currently available agents. NAFLD therapies target four main pathways. The dominant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
302
0
13

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(331 citation statements)
references
References 125 publications
(120 reference statements)
6
302
0
13
Order By: Relevance
“…The synthetic FXR agonist GW4064 was able to prevent liver steatosis in obese mice, such as the ob/ob and db/db models [34]. Based on this finding, obeticholic acid (OCA) was proposed for the treatment of NASH as a synthetic FXR agonist [35]. A phase 2 trial showed that administration of OCA at 25 mg or 50 mg daily for 6 weeks reduced markers of liver inflammation and fibrosis and increased insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The synthetic FXR agonist GW4064 was able to prevent liver steatosis in obese mice, such as the ob/ob and db/db models [34]. Based on this finding, obeticholic acid (OCA) was proposed for the treatment of NASH as a synthetic FXR agonist [35]. A phase 2 trial showed that administration of OCA at 25 mg or 50 mg daily for 6 weeks reduced markers of liver inflammation and fibrosis and increased insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…While available data of its benefit in NASH is limited, a double blind placebo controlled trial of saoglitazor in NASH is currently underway in India (Clinical Trials Registry-India CTRI/2015/10/006236). 85 …”
Section: (B) Peroxisome Proliferator-activated Receptors (Ppar) Agonistsmentioning
confidence: 99%
“…Two strategies directly aiming at preventing and reducing fibrosis in NASH are in clinical development with the caspase inhibitor emricasan in phase IIa and galectin 3 inhibitors in phase I [228,229,[232][233][234]. Although there is also some limited evidence that PPARγ activation itself might have anti-fibrotic activity [235], combination of anti-fibrotic approaches with PPAR agonists holds therapeutic promise.…”
Section: Dual Ppar Agonists Clinical Trialsmentioning
confidence: 99%
“…Several anti-inflammatory targets have already proven efficacy against this aspect of NASH in animal models or even clinical trials. Except for the anti-oxidative activity of vitamin E, two anti-inflammatory strategies evolve as experimental approaches in NASH treatment [12,228,229]. The chemokine receptor antagonist cenicriviroc blocking the chemokine receptors (CCR)2 and CCR5 is currently the most advanced anti-inflammatory agent in the NASH pipeline.…”
Section: Dual Ppar Agonists Clinical Trialsmentioning
confidence: 99%